Hiperrealitas dalam Media Sosial - Chairunnisa, Amadona Farninda; Mayasari, Mayasari; Lubis, Fardiah Oktariani (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
This study reviews the phenomenon of hyperreality which has now become part of people's lifestyles, especially social media users, namely the phenomenon of makan cantik. This study uses a qualitative method to view and describe the process of makan cantik on social media among female students of the 2019 Communication Science Study Program, Singaperbangsa Karawang University as a hyperreality phenomenon. This study aims to determine whether there is a value discrepancy between what is uploaded on social media, and what actually is. Makan cantik is a simulation activity to show a certain image through social media which is considered to represent an upper-class lifestyle. Makan cantik often try to display only the best sides of food uploaded on social media which can not only increase the attractiveness of food and public interest in the food, but also show a classy lifestyle side. Where in the makan cantik activities that are uploaded on social media, there are conditions that turn out to be different from the reality. Where they will create video or photo content that shows the side of pleasure to the quality of the food that is uploaded. Therefore, currently social media no longer always displays reality so that the phenomenon of hyperreality is created. Keywords: hyperreality, beautiful eating, social media